Positronium scattering by a hydrogen molecule including exchange - Biswas, P. K.; Adhikari, S. K. (Iop Publishing Ltd, 1998)
We perform a three-positronium (Ps) state [Ps(ls,2s,2p)] coupled-channel calculation of Ps-H-2 scattering including the effect of electron exchange. At medium energies, higher excitations and ionization of Ps are treated within the framework of the first Born approximation. In both cases exchange is included using a recently proposed nonlocal model exchange potential which is free of non-orthogonality problems common in the usual antisymmetrization scheme. The present total cross sections at low and medium energies are in encouraging agreement with experiment.